Caprella scaura Templeton, 1836 sensu lato (Amphipoda: Caprellidae) in the Mediterranean - Krapp, T.; Lang, C.; Libertini, A.; Melzer, R. (Organisms Diversity & Evolution, 2006)
Caprella scaura, first described from Mauritius and later reported in several ‘forms’ from all over the world, has now been found in the central and eastern Mediterranean. The morphology shows no significant difference to the topotypical material. Specimens from Venice and Sicily have been studied in detail, the former also by cytogenetic methods.